Prandtl-Essentials of Fluid Mechanics - Oertel, Herbert; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Ludwig Prandtl, with his fundamental contributions to hydrodynamics, aerodynamics and gasdynamics, greatly influenced the development of fluid mechanics as a whole and it was his pioneering research in the first half of the 20th century that founded modern fluid mechanics. His book `Fuhrer durch die Stromungslehre$1 (Bor `Essentials of Fluid Mechanics$1 (Bappeared in 1942. Even today it is considered one of the most important books in the area. It is based on the 12th German edition with additional material included. All Chapters have been revised and extended, and there are new chapters on fluid mechanical instabilities and turbulence, microflows and biofluid mechanics. Essentials of Fluid Mechanics is aimed at science and engineering students and researchers wishing to obtain an overview of the different branches of fluid mechanics. The book is extensively illustrated throughout and includes problems to aid learning in many chapters. Reviews of previous edition: The range of topics considered in this volume is impressive and physical ideas and principles described and illustrated by a wide range of examples will make this book interesting to students and specialists in various fields. --Contemporary Physicss
Properties of Liquids and Gases -- Kinematics of Fluid Flow -- Dynamics of Fluid Flow -- Fundamental Equations of Fluid Mechanics -- Instabilities and Turbulent Flows -- Convective Heat and Mass Transfer -- Multiphase Flows -- Reactive Flows -- Flows in the Atmosphere and in the Ocean -- Microflows -- Biofluid Mechanics.
Keywords: Physics; Mathematics; Engineering mathematics; Physics; Classical Continuum Physics; Theoretical, Mathematical and Computational Physics; Appl.Mathematics/Computational Methods of Engineering; Applications of Mathematics